Associations between temporal eating patterns and energy distribution patterns with gallstones: a cross-sectional study based on NHANES 2017-2018 - Huan Zhang; Chao Xu; Xiaojing Zhu; Ju Zhang; Jumei Yin; Nuo Yao; Qimeng Pang; Zhihua Liu; Chenchen Wang; Dawei Wu; Yongquan Shi; Lei Shang; et al. (BMC, 2024)
Abstract Background Gallstones are strongly associated with eating occasion (EO) and energy distribution, but few studies have addressed this aspect. Therefore, we utilize the data from 2017 to 2018 National Health and Nutrition Examination Survey (NHANES) to explore the association between temporal eating patterns and energy distribution patterns with the incidence of gallstones. Methods Our study comprised participants who completed the NHANES dietary intake interview and self-reported health questionnaire at age 20 or older. The self-report method for gallstones (have you ever been told by a doctor) was used. We use the latent class analysis (LCA) identified temporal eating patterns, and identified energy distribution patterns through latent profile analysis (LPA). The association between temporal eating patterns, energy distribution patterns, and gallstones was examined using logistic regression modeling. Results The study included a total of 4,692 participants. LCA identified four temporal eating patterns labeled as "Conventional," "Early breakfast," "Later breakfast," and "Grazing." Compared to the "Conventional" pattern, the "Early breakfast" pattern (OR 0.809, 95%CI 0.808-0.811) was associated with a reduced risk of gallstones, while the "Later breakfast" (OR 1.435, 95%CI 1.432-1.438) and "Grazing" (OR 1.147, 95%CI 1.145-1.148) patterns were associated with an increased risk of gallstones. LPA identified four energy distribution patterns labeled as "Guideline," "High carbohydrates," "Carbs-fat balance," and "High fat." The "High carbohydrates" pattern (OR 1.329, 95%CI 1.326-1.331) was associated with an increased risk of gallstones compared to the "Guideline" pattern. The "Carbs-fat balance" pattern (OR 0.877, 95%CI 0.876-0.879) and the "High fat" pattern (OR 0.848, 95%CI 0.846-0.850) were significantly and negatively associated with the risk of gallstones. Conclusions To summarize, inappropriate timing of eating and energy sources are associated with gallstones. As a dietary prevention measure for gallstones, we suggest adhering to a regular eating routine and avoiding overly casual and frequent food consumption. If the main EO routine occurs in the morning, this time should not exceed 9:00 a.m. Additionally, reducing carbohydrate intake and maintaining a moderate level of fat intake is believed to contribute to a lower risk of gallstones.